Correct Botanical Name of ’Langsat’ - Sahni, K. C.; Bennet, S. S. R. (Indian Forester, 1974)
Scleria psilorrhiza is reported from Himachal Pradesh. It is a stoloniferous sedge, having premorse leaves with the leaf sheaths conspicuously winged. Inflorescence is a terminal panicle. Nut is ovoid, 3.5-4 mm long, smooth, shining, hard, not beaked; disk triangular, reflexed, shallowly and obtusely 3-lobed.